2017
DOI: 10.1002/ejic.201701150
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity and Microstructural Versatility in the Spin‐Crossover Polymeric Material [Fe(Htrz)2(trz)](BF4)

Abstract: Abstract:The room-temperature microstructure of the spincrossover (SCO) 1D polymeric iron(II) compound [Fe(Htrz) 2 (trz)](BF 4 ) has been investigated by means of powder X-ray diffraction and compared with the SCO features determined by magnetic measurements. The microstructural parameters, such as the sizes of the coherent domains, of a number of samples and their morphologies have revealed new features of this material. Heating can significantly improve the crystalli-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…The spin transition phenomenon known as spin-crossover (SCO) was originally observed more than 85 years ago [1]. Since that time, there have been numerous studies on compounds that undergo this spin transition phenomenon [2][3][4][5][6][7][8][9][10][11][12][13][14]. A spin transition is an example of electronic bistability at the molecular level impacted by the coordinating ligands.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spin transition phenomenon known as spin-crossover (SCO) was originally observed more than 85 years ago [1]. Since that time, there have been numerous studies on compounds that undergo this spin transition phenomenon [2][3][4][5][6][7][8][9][10][11][12][13][14]. A spin transition is an example of electronic bistability at the molecular level impacted by the coordinating ligands.…”
Section: Introductionmentioning
confidence: 99%
“…This bistable SCO compound [Fe(Htrz) 2 (trz)](BF 4 )] can exist in two interchangeable states depending on the external stimuli. The electronic configurations of the Fe(II) in this system can be switched between low spin and high spin states, using stimuli such as temperature [16], irradiation [16], and magnetic fields [8]. This low to high spin transition or vice versa impacts various properties within the material, including optical, magnetic, mechanical, and electrical characteristics [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Such materials would combine the molecular order of single crystals with the properties of soft matter. [4] Av ariety of crystalline materials that display stimuliresponsive behaviour, [5] including breathable metal-organic frameworks, [6] spin-crossover materials, [7] thermosalience, [8] mechanosalience, [9] and photosalience [10] have been reported along with examples of both plastically [11] and elastically flexible crystals. [3a,8b, 12] Often, the fundamental mechanisms that lead to this behaviour are not well understood [11d,13] even though such materials may have applications in diverse areas from precision engineering to flexible electronics.…”
mentioning
confidence: 99%
“…We synthesized also the corresponding imino complex by direct synthesis (DS) starting from the imino ligand (see ESI) in order to compare its properties with those of the post-synthetic imino complex. It is well known that the SCO behaviour is strongly dependent of different structural factors such as crystallinity 15 or polymorphism. 16 Interestingly, we found that in contrast with the post synthetic reaction, the direct synthesis of the imino complex when carried out in the normal stirring conditions, resulted systematically in an amorphous powder (6); it was necessary to use a solvent diffusion technique in order to obtain a crystalline powder (7) as shown in figure 1, this is important in order to make a fair structure-properties relationship.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%